Shaping the System – The DRG Evaluation Project of the German Society for Gynaecology and Obstetrics (Deutsche Gesellschaft für Gynäkologie und Geburtshilfe, DGGG) - Fiori, W.; Renner, S. P.; Siam, K.; Babapirali, J.; Roeder, N.; Dausch, E.; Hildebrandt, T.; Hillemanns, P.; Nehmzow, M.; Zygmunt, M.; Piroth, D.; Schem, C.; Schwenzer, T.; Friese, K.; Wallwiener, D.; Beckmann, M. W. (Geburtshilfe und Frauenheilkunde, 2013)
Introduction: The German DRG system is annually adapted to the changing services provided. For the further development, the self-governing body and its DRG Institute (InEK) depend on participation of the users. Methods: For one of the DRG evaluation projects initiated by DGGG, cost and performance data for the year 2011 from 16 hospitals were available. After plausibility checks and corrections, analyses for service and cost homogeneity were performed. In cases of inadequate DRG-representation attributes were sought that would make an appropriate reimbursement possible. Conspicuities and potential solutions were checked for clinical plausibility. Results: 44 concrete modification proposals for further development of the G-DRG system were formulated and submitted in due time to the InEK. In addition, 3 modification proposals were addressed to the German Institute for Medical Documentation and Information (Deutsches Institut für Medizinische Dokumentation und Information, DIMDI) for further development of the diagnosis classification ICD-10-GM. For all modification proposals care was taken to minimise misdirected incentives and to reduce the potential for disputes with the cost bearers and their auditors services in settlements. Discussion: The publication of the G-DRG system 2014 shows which modification proposals have been realised. Essentially, an appropriate redistribution of the resources among the gynaecological and obstetrics departments is to be expected. The financial pressure that is caused by the generally inadequate financing of hospitals will not be reduced by a further development of the G-DRG system.
Keywords: DRG; quality assurance; coding; DGGG; MDC; adaptation